Examining the different leadership styles on turnover intention - Shamsudin, Azlina; Mat Zin, Sakinah (Journal of Islamic, Social, Economics and Development, 2025)
Organization performance will be affected when there is a high number of employee turnover. One of the factors that influence turnover intention is leadership style. This study will specifically be focusing on Path-Goal Theory (PGT) which consists of four leadership styles. When employees feel comfortable with the organization environment, they will feel satisfied and least likely to think about turnover. The objective of this study is to investigate the relationship between turnover intention and leadership styles, with job satisfaction acting as the mediator. Grounded on the Path-Goal Theory (PGT) and Social Exchange Theory (SET), this study proposes a quantitative research approach that involves academic staff from private higher education institutions as respondents. The method of simple random sampling will be implemented. Subsequently, this study intends to employ Smart Partial Least Squares (SmartPLS) to scrutinize the data and evaluate the hypothesis development. This study highlights the importance of promptly undertaking a study on the impact of leadership style on academic staff to decrease the rate of turnover at private higher education institutions.